2022
DOI: 10.1007/s43441-022-00397-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Lead to Stagnation in Direct Patient Reporting of Adverse Drug Reactions: An Opinion Survey of the General Public and Physicians in Japan

Abstract: Objective Data collection from patients regarding adverse drug reactions (ADRs) in Japan have greatly stagnated. To examine the factors underlying this stagnation, we investigated the awareness of and opinions about the direct ADR reporting system among the general public and physicians. Methods We conducted questionnaire surveys of general citizens and physicians throughout Japan and included the following topics: (1) awareness of the direct patient ADR reporting syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a separate study conducted in Japan, 845 citizens were found unaware of the direct patient ADR reporting system (Kitabayashi & Inoue, 2022). One other concern, patients may believe that public reporting of drug-related problems may affect the physician-patient relationship, which is proven by these studies (Kitabayashi & Inoue, 2022) (Inácio et al, 2017). On the other hand, in 2018, a cross-sectional survey among 360 patients in Nigeria demonstrated a low level of awareness of pharmacovigilance and ADR reporting (Adisa & Omitogun, 2019).…”
Section: Factors Affecting Patient Reporting Of Adverse Drug Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study conducted in Japan, 845 citizens were found unaware of the direct patient ADR reporting system (Kitabayashi & Inoue, 2022). One other concern, patients may believe that public reporting of drug-related problems may affect the physician-patient relationship, which is proven by these studies (Kitabayashi & Inoue, 2022) (Inácio et al, 2017). On the other hand, in 2018, a cross-sectional survey among 360 patients in Nigeria demonstrated a low level of awareness of pharmacovigilance and ADR reporting (Adisa & Omitogun, 2019).…”
Section: Factors Affecting Patient Reporting Of Adverse Drug Reactionsmentioning
confidence: 99%
“…In 2012, a cross-sectional study was conducted in Saudi Arabia which revealed that the public lacked awareness about ADRs and had limited knowledge on how to report them (Sales et al, 2017). In a separate study conducted in Japan, 845 citizens were found unaware of the direct patient ADR reporting system (Kitabayashi & Inoue, 2022). One other concern, patients may believe that public reporting of drug-related problems may affect the physician-patient relationship, which is proven by these studies (Kitabayashi & Inoue, 2022) (Inácio et al, 2017).…”
Section: Factors Affecting Patient Reporting Of Adverse Drug Reactionsmentioning
confidence: 99%